The effects of Individual & Collective competition pattern on improving the spike and block skills and their retention in volleyball of the students - Aldulaimi, Nahida (Journal of Physical Education, 2009)
The purpose of this research was to examine the effects of both individual & collective competition patterns on improving the spike & block skills in the volleyball students, besides of the ability of their retention rate to perform these skills. Methods: 36 students of fourth-stage College of physical education were selected at random way as subjects in this research and assigned to tow experimental groups, group one served the individual competition method, the other used the collective competition method. Both groups were tested pre & post training in the concerning method , under same conditions , which performed an exercise protocol one time/week for 6 weeks , and the results were analyzed statically as well.Results:The investigator found that both individual & collection completion methods had a reasonable effects on improving spike & block skills, but with different ratio . Yet using collective competition method had a significant value than the other, besides of its effects of retention. So, the investigator recommends using these methods to improve the spike & block skills in volleyball for the fourth-stage students, also, recommends teachers who training this kind of sport to pay attention to serve these methods in their working in the collage of physical education, as well.